The effect of the structured inquiry learning model on students' critical and collaborative thinking skills - Laely Faizati Al Hidayah; Tutut Nurita (Jurnal Pijar Mipa, 2022)
The study aims to describe the effect of the inquiry learning model on student critical thinking skills and collaborative skills. The one-group pretest-posttest design was used in the study. The samples were 31 students in grade eight of junior high school in Surabaya, Indonesia. Learning performance data is obtained through observation methods, students' critical thinking skills data through writing test methods, and collaborative skills with observation methods. Learning implementation data is then analyzed with mode formulas. Critical thinking skill data is analyzed using the paired-sample t-test. Collaboration skill data is analyzed with the mode formula. Critical thinking skills indicators are providing simple explanations, building basic skills, concluding, providing advanced explanations, and organizing strategies and tactics. Collaborative skill indicators are working productively with a group of friends, being jointly responsible for getting work done, participating respectfully in discussions, debates, and disagreements, committing to putting group goals first, showing flexibility, and compromising. The study showed that tcount=12.961 and ttable=30. It means that a structured inquiry learning model can improve students' critical and collaborative thinking skills.